Promoting the integration of payment markets: A stakeholder’s vision - Domingos, M. M.; António, N.; Pinheiro, C. (European Business Organization Law Review, 2023)
We validate stakeholder theory using a natural experiment in the European payments industry, the Single Euro Payments Area (SEPA), supported by unique primary data. SEPA is an important part of the single European market, on the back of the creation of the single currency in 1999. SEPA created a new environment of competition across Europe by making national borders irrelevant. Interviews with Portuguese experts directly involved in the realization of SEPA make it possible for us to provide a new taxonomy of stakeholders according to their power and role. Our study highlights the association between stakeholder theory and a strategic project at the European level and invites further research on the theoretical underpinnings of large-scale ventures.